Next-generation sequencing yields the complete chloroplast genome of C. goeringii acc. smg222 and phylogenetic analysis. Issue 1 (2nd January 2018) - Wang, Heng; Park, So-Yeon; Lee, Ah-Rim; Jang, Seong-Gyu; Im, Da-Eun; Jun, Tae-Hwan; Lee, Joohyun; Chung, Jong-Wook; Ham, Tae-Ho; Kwon, Soon-Wook
Abstract: Spring orchid ( Cymbidium goeringii ) is one of the most important species belonging to Orchidaceae owing to its aesthetic appeal, fragrant flowers and ideal characteristics for using as a houseplant. In this study, the complete chloroplast genome of Korean C. goeringii acc. smg222 was determined by Illumina sequencing. The circular double-stranded DNA of 148, 441 bp consisted of two inverted repeat regions of 25, 610 bp each, a large single copy region of 83, 311 bp, and a small single copy region of 13, 910 bp. The genome contained 122 genes, of which 104 were unique and 18 were duplicated within the IRs. The 104 unique genes included 70 protein-coding genes, 30 distinct tRNA genes, and four rRNA genes. Phylogenetic tree analysis revealed that C. goeringii acc. smg222 was clustered with Cymbidium kanran, a cymbidium species native to Korea.